What you need to know about marketing - Middleton, Simon (West Sussex : Capstone, 2011)
Shows you how to understand and do marketing without having to study a degree or a diploma in it. Along the way it shows you what has been learned about marketing over the centuries, what experts can teach us that we can use ourselves, how marketing has changed in our new 'digital' world, and more.
Includes bibliographies and Index.
Keywords: Marketing; Marketing -- Management